Risk Disclosure dan Kinerja Perusahaan dengan Corporate governance sebagai Variabel Moderasi - Restika, Amalia; Lastiati, Anies (E-Jurnal Akuntansi, 2021)
This study aims to examine the effect of risk disclosure to firm performance. It further examines whether corporate governance (Board of commisioner, independent comminisioner, andgaudit committee) moderates the relationship between risk disclosure and firm performance. The sources of this study were manufacturing companies listed on Indonesia Stock Exchange in 2017 – 2018. The number of samples was 174 companies, with a purposive sampling method. The technique of analysis uses confimatory analysis factor (CFA), classic assumption tst, and multiple linear regression test. The results show that risk disclosure has a positive influence on the firm performance. Furthermore results shows that board of commissioner and independent commisioner strengthen the relationship between risk disclosure and firm performance. This role, however is not found in the corporation’s audit committee. The committee does not have any impact whatsoever to the relationship between risk disclosure and coporates’ performance.  Keywords: Corporate Governance; Firm Performance; Risk Disclosure.